Switchable Chiral Mirrors. Issue 15 (7th May 2020) - Liu, Meng; Plum, Eric; Li, Hua; Duan, Siyu; Li, Shaoxian; Xu, Quan; Zhang, Xueqian; Zhang, Caihong; Zou, Chongwen; Jin, Biaobing; Han, Jiaguang; Zhang, Weili
Abstract: Mirrors are widely used for redirection of electromagnetic waves in optical systems, making them arguably the most irreplaceable optical component. Metamaterial‐based chiral mirrors, composed of a 2D‐chiral planar metallic structure backed by a conventional mirror, reflect one circular polarization without changing its handedness, while absorbing the other. Here, three types of switchable chiral mirror are demonstrated. Switching from a chiral mirror to either a conventional mirror, a handedness‐preserving mirror, or a chiral mirror of opposite handedness, is realized. These advances are underpinned by switching the handedness of 2D‐chiral metamaterial and the associated effect of circular conversion dichroism, which is reported here for the first time. Switching is achieved by exploiting the temperature‐activated dielectric‐to‐metal phase transition of vanadium dioxide to modify the symmetry and chirality of the metamaterial's resonators. Current distributions explain the temperature‐controlled optical properties by handedness‐selective excitation of reflective electric dipole and absorbing magnetic dipole modes. Abstract : Phase transitions enable active control over chirality and anisotropy of matter. This opportunity is exploited to switch electromagnetic functions of artificial materials by realizing the first switchable chiral mirrors. Switching from a chiral mirror to either a conventional mirror, a handedness‐preserving mirror, or a chiral mirror of opposite handedness is demonstrated.